REPRESENTASI RASISME DALAM FILM PENDEK SKIN (ANALISIS SEMIOTIKA ROLAND BARTHES) - Duta Prasatya, I Gede Anang; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2020)
ABSTRACT Racism is a belief that considers one racial group to be superior to other racial groups. The issue of racism can be presented through films, as in the short film Skin. The short film Skin depicts a white group who assault a black man at a convenience store. The purpose of this study is to find out how racism is represented in the short film Skin. This study uses a qualitative approach and analyzed using the semiotic analysis of Roland Barthes which consists of denotations, connotations and myths. The results of this study indicate that the short film Skin represents racism in the form of prejudice, stereotypes and discrimination. Black people receive prejudice as a threat and a criminal, dangerous stereotypes, discrimination in the form of ridicule, use of the terms negro and jigaboo, and assaults against blacks. Key w ords: Racism, Representation, Semiotics, Film